2016
DOI: 10.1186/s13063-016-1676-7
|View full text |Cite
|
Sign up to set email alerts
|

StereoTactic radiotherapy for wet Age-Related macular degeneration (STAR): study protocol for a randomised controlled clinical trial

Abstract: BackgroundThe standard of care for neovascular age-related macular degeneration (nAMD) involves ongoing intravitreal injections of anti-angiogenic drugs targeting vascular endothelial growth factor (VEGF). The most commonly used anti-VEGF drugs are ranibizumab, bevacizumab and aflibercept. The main objective of the STAR trial is to determine if stereotactic radiotherapy can reduce the number of anti-VEGF injections that patients with nAMD require.Methods/designSTAR is a multicentre, double-masked, randomised, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…These aspects need to be evaluated in a prospective trial, and the currently ongoing STAR study might answer these questions. 30 As we did not follow patients without anti-VEGF treatment after SRT within our analysis, it is not possible to distinguish between the "SRTonly" drying effect or the possibility of anti-VEGFfacilitating effects of SRT. Concerning safety outcomes in terms of microvascular abnormalities, the follow-up period in the analysis was too short to allow for assessments, and these changes may not be detected on clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects need to be evaluated in a prospective trial, and the currently ongoing STAR study might answer these questions. 30 As we did not follow patients without anti-VEGF treatment after SRT within our analysis, it is not possible to distinguish between the "SRTonly" drying effect or the possibility of anti-VEGFfacilitating effects of SRT. Concerning safety outcomes in terms of microvascular abnormalities, the follow-up period in the analysis was too short to allow for assessments, and these changes may not be detected on clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high cost of the drugs, it is imperative that clinical services are organised to deliver care efficiently. For example, nurse-administered injections, 36 treat and extend protocols, 37 optometrist-led monitoring 38 and stereotactic radiotherapy, 39 all offer the potential to reduce costs and require stronger evidence. The wide variation between CCGs in the number of injections per patient represents a natural experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Other treatment modalities under investigation include the role of adjunctive treatments alongside anti-VEGF by stereotactic radiotherapy (ie, use of a low-voltage external beam) to reduce the frequency of intravitreal injections needed while maintaining VA. 175 , 176 Ranjbar et al 177 demonstrated that the mean number of intravitreal injections was reduced by almost 50% during the 12 months after stereotactic radiotherapy compared to the number required the year before and that VA increased by one line (logMAR). Other promising therapeutic approaches are modulators of angiogenesis.…”
Section: Treatment Of Wet Amdmentioning
confidence: 99%